The Utility of Computed Tomographic Angiography in Preoperative Planning of Deep Inferior Epigastric Artery Flap - Aziminezhadan, Parisa; Lepage, Christophe; pigneur, Frederic; Lantieri, Laurent (Reports of Radiotherapy and Oncology, 2023)
Background: Abdominal donor site flaps are the standard for autologous breast reconstruction. Because of extreme variations of abdominal wall vascular anatomy between individuals, and even two hemi-abdomens of the same person, it seems valuable to use a sensitive method for preoperative evaluation. In this study, we evaluated the effects of preoperative abdominal wall computed tomographic angiography (CTA) in women who had undergone delayed unilateral breast reconstruction with abdominal perforator flaps. Methods: Between October 2007 and June 2008, 24 women with breast cancer were admitted to Henri Mondor General Hospital, Creteil, France, for breast reconstruction. We used CTA to identify the perforator vessels for dissection and compared the results with other previously used techniques. Results: There was an absolute correlation between the radiological information and intraoperative findings. An average of one hour was saved in delayed unilateral breast reconstruction with deep inferior epigastric artery perforator flap by using CTA preoperatively. Conclusion: Computed tomographic angiography provides valuable preoperative information in identification of the most suitable perforator, and its use before abdominal flaps breast reconstructions could be recommended.